Narrative Policy Framework: Analysis of Policy Discourse for the Three-Term Presidential Term - Syukri, Ahmad; Al-Hamdi, Ridho; Suswanta, Suswanta; Kurniawan, Danang (Journal of Government and Civil Society, 2023)
The discourse on the policy of a three-term presidential term raises pros and cons in the political circles of the government and the people of Indonesia. The narrative can be seen through the opinions of policy actors, government, political parties, Non-Governmental Organizations (NGOs), and the community. This study uses a method with a Q-DAS (Qualitative Data Analysis Software) approach. The data in the study were taken through four national online news media with a high level of credibility. This research will conduct a study using the Narrative Policy Framework (NPF) which can explain the structure of the political narrative in the policy-making process of changing the President's term of office. This study aims to examine the role of the media in shaping public narratives in formulating policies for the Presidential General Election in Indonesia. The results of this study indicate that the votes in the group that is against the narrative of the presidential term policy are more dominant for three periods. President Joko Widodo's firm refusal was able to influence the intensity of the discussion on the policy to increase the President's term of office.Wacana kebijakan masa jabatan presiden tiga periode menimbulkan pro dan kontra di kalangan politik pemerintah dan masyarakat Indonesia. Narasi tersebut dapat dilihat melalui pendapat dari aktor-aktor kebijakan, pemerintah, partai politik, Lembaga Swadaya Masyarakat (LSM), dan masyarakat. Penelitian ini menggunakan metode dengan pendekatan Q-DAS (Qualitative Data Analysis Software). Data pada penelitian diambil melalui empat media berita online nasional dengan tingkat kredibilitas yang tinggi. Penelitian ini akan melakukan studi menggunakan Narrative Policy Framework (NPF) yang dapat menjelaskan bagaimana struktur narasi politik pada proses pembuatan kebijakan perubahan masa jabatan Presiden. Penelitian ini bertujuan untuk melihat peran media dalam membentuk narasi publik dalam penyusunan kebijakan Pemilihan Umum Presiden di Indonesia. Hasil pada penelitian ini menunjukkan bahwa suara pada kelompok yang kontra terhadap narasi kebijakan masa jabatan presiden menjadi tiga periode lebih dominan. Penolakan secara tegas yang disampaikan oleh Presiden Joko Widodo mampu mempengaruhi intensitas pembahasan wacana kebijakan penambahan masa jabatan Presiden.